Characteristics and risk factors for readmission in HIV-infected patients with Talaromyces marneffei infection. - Minjuan Shi; Yaqin Qin; Shanshan Chen; Wudi Wei; Sirun Meng; Xiaoyu Chen; Jinmiao Li; Yueqi Li; Rongfeng Chen; Jinming Su; Zongxiang Yuan; Gang Wang; et al. (Public Library of Science (PLoS), 2023)
Objectives Talaromyces marneffei (T. marneffei) is an opportunistic fungal infection (talaromycosis), which is common in subtropical regions and is a leading cause of death in HIV-1-infected patients. This study aimed to determine the characteristics and risk factors associated with hospital readmissions in HIV patients with T. marneffei infection in order to reduce readmissions. Methods We conducted a retrospective study of admitted HIV-infected individuals at the Fourth People's Hospital of Nanning, Guangxi, China, from 2012 to 2019. Kaplan-Meier analyses and Principal component analysis (PCA) were used to evaluate the effects of T. marneffei infection on patient readmissions. Additionally, univariate and multifactorial analyses, as well as Propensity score matching (PSM) were used to analyze the factors associated with patient readmissions. Results HIV/AIDS patients with T. marneffei-infected had shorter intervals between admissions and longer lengths of stay than non-T. marneffei-infected patients, despite lower readmission rates. Compared with non-T. marneffei-infected patients, the mortality rate for talaromycosis patients was higher at the first admission. Among HIV/AIDS patients with opportunistic infections, the mortality rate was highest for T. marneffei at 16.2%, followed by cryptococcus at 12.5%. However, the readmission rate was highest for cryptococcus infection (37.5%) and lowest for T. marneffei (10.8%). PSM and Logistic regression analysis identified leukopenia and elevated low-density lipoprotein (LDL) as key factors in T.marneffei-infected patients hospital readmissions. Conclusions The first admission represents a critical window to intervene in the prognosis of patients with T. marneffei infection. Leukopenia and elevated LDL may be potential risk factors impacting readmissions. Our findings provide scientific evidence to improve the long-term outcomes of HIV patients with T. marneffei infection.